EXPLORING TEACHERS’ EXPERIENCES IN DELIVERING SEXUAL AND REPRODUCTIVE HEALTH EDUCATION TO STUDENTS WITH LEARNING DISABILITIES IN SOUTHERN SARAWAK - Shaadah, Shariman; Faizah, Haji Masud (Malaysian Paediatrics Association (MPA)., 2025)
This study investigates the experiences of teachers delivering sexual and reproductive health (SRH) education to students with intellectual disabilities in southern Sarawak, Malaysia. It explores the challenges and strategies within Malaysia's socio-cultural framework. Methods: Employing a phenomenological approach, the study conducted in-depth, semi-structured interviews with ten educators from Kuching, Kota Samarahan, Padawan, Bau, and Serian. Participants had over two years of experience in special education and SRH instruction. Giorgi’s five-step phenomenological method was used for data analysis.Results: Teachers reported significant challenges, including adapting SRH content to diverse cognitive abilities, addressing cultural and familial resistance, and navigating inadequate training and resources. Effective strategies identified included repetitive, tailored instruction, culturally sensitive framing of lessons, and embedding SRH into daily classroom interactions. Conclusions: Findings emphasize the need for culturally aligned SRH curricula that integrate life skills and support professional development for educators. These insights offer a foundation for policy enhancements, advocating for an inclusive SRH framework within Malaysia’s special education system.